2022
DOI: 10.3389/fphys.2022.951899
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular electrical stimulation to augment lower limb exercise and mobility in individuals with spastic cerebral palsy: A scoping review

Abstract: Background: Neuromuscular Electrical Stimulation (NMES) is an emerging assistive technology applied through surface or implanted electrodes to augment skeletal muscle contraction. NMES has the potential to improve function while reducing the neuromuscular impairments of spastic cerebral palsy (CP). This scoping review examines the application of NMES to augment lower extremity exercises for individuals with spastic CP and reports the effects of NMES on neuromuscular impairments and function in spastic CP, to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 88 publications
(201 reference statements)
0
4
0
Order By: Relevance
“…Furthermore, recent evidence from systematic reviews and other studies supports using NMES for strengthening in individuals with spastic CP, to improve mobility and gross motor function, and safely induce restorative changes. 43 , 44 , 45 , 46 …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recent evidence from systematic reviews and other studies supports using NMES for strengthening in individuals with spastic CP, to improve mobility and gross motor function, and safely induce restorative changes. 43 , 44 , 45 , 46 …”
Section: Discussionmentioning
confidence: 99%
“…Children with SCP usually have increased lower limb muscle tone, decreased muscle strength, limited gross motor function, and impaired gait and balance. 58 These symptoms can severely affect a child's ability to walk and make it difficult for the child to participate in daily activities comparable with those of their typically developing peers. This study confirmed the effectiveness of nonimmersive VR in the rehabilitation of children with spastic cerebral palsy.…”
Section: Discussionmentioning
confidence: 99%
“…NMES applications include the use of NMES-assisted strengthening, NMESassisted gait, and NMES spasticity reduction. [30][31][32]…”
Section: Physical Therapymentioning
confidence: 99%
“…Electrodes are commonly placed over the motor point where the motor nerve innervates the muscle. NMES applications include the use of NMES‐assisted strengthening, NMES‐assisted gait, and NMES spasticity reduction 30–32 …”
Section: Respiratory Physiotherapy (Rp)mentioning
confidence: 99%